Peningkatan Kualitas Produk Melalui Penerapan Teknologi Ruang Oven di Industri Jasa Finishing Mebel - Achmad Zainudin; Nur Aeni Widiastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Sukosono Village is located in Kedung District, Jepara Regency. There are 9 Furniture Finishing Services businesses. To purchase furniture products, buyers can buy ready-made products or products that have not been finished or what is usually called raw. To purchase raw products, buyers must go to a finishing service to process the final product to make it better. HD Furniture is a business group engaged in finishing services in Sukosono village which the team will make a partner in this service. Production per day can produce 5-6 products. For marketing areas in Jepara and Palembang. The problems that exist for Partners are: (1) Orders are increasing but the equipment they have for the production process has low capacity, (2) at the spraying stage (coating) there are still problems with humidity resulting in finishing defects (condensation, white spots on the surface layer of the product) , (3) Layout and Quality Control are still minimal. The solution offered is socialization and assistance in making oven room technology for post-finishing, workshops on finishing techniques, workshops on layout and quality control. The output of this activity is that production capacity and quality product has been increased by 100%, and Human Resource skills have increased by 100%.